2023
DOI: 10.1002/fee.2635
|View full text |Cite
|
Sign up to set email alerts
|

What's in a name? The paradox of citizen science and community science

Abstract: Citizen science has expanded ecological and environmental sciences by actualizing studies across greater spatial and temporal scales while incorporating local expertise and interests that might otherwise be overlooked. Broadly, citizen science involves the public in the process of science. However, it continues to struggle to engage diverse participants. Citizen science project coordinators are increasingly trying to promote inclusivity by rebranding as community science to avoid the term citizen. Although wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Although the issue of terminology has been present in the field of citizen science since the beginning, it has been hotly debated recently with discussions held at the major science communication and citizen science conferences in 2023 (Roche et al, 2023). One of the central issues of the terminology debate-the distinction between citizen science and community science and how the "citizen" term can be insensitive to marginalised communities (Ellwood et al, 2023;Lin Hunter et al, 2023)-culminated in the USbased but globally-reaching Citizen Science Association changing its name to "the Association for Advancing Participatory Sciences". While there is no doubt that inclusion needs to be improved in the field (Cooper et al, 2021), some citizen science scholars have suggested that the field can be made more inclusive without resorting to abandoning a term that has gradually been gaining in scientific and political credibility in recent years (Haklay, 2023).…”
Section: Citizen Science: Public Participation In Sciencementioning
confidence: 99%
“…Although the issue of terminology has been present in the field of citizen science since the beginning, it has been hotly debated recently with discussions held at the major science communication and citizen science conferences in 2023 (Roche et al, 2023). One of the central issues of the terminology debate-the distinction between citizen science and community science and how the "citizen" term can be insensitive to marginalised communities (Ellwood et al, 2023;Lin Hunter et al, 2023)-culminated in the USbased but globally-reaching Citizen Science Association changing its name to "the Association for Advancing Participatory Sciences". While there is no doubt that inclusion needs to be improved in the field (Cooper et al, 2021), some citizen science scholars have suggested that the field can be made more inclusive without resorting to abandoning a term that has gradually been gaining in scientific and political credibility in recent years (Haklay, 2023).…”
Section: Citizen Science: Public Participation In Sciencementioning
confidence: 99%
“…Second, the definition and selection of citizen science projects arguably affect the results as well as the transferability of results to other citizen science projects (Eitzel et al, 2017). Likewise, terminologies are constantly evolving and subject to ongoing discussion (Auerbach et al, 2019;Heigl et al, 2019;Haklay M. et al, 2021;Lin Hunter et al, 2023). This study focused on contributory citizen science projects in the field of water monitoring.…”
Section: Implications Of Findings Considering Potential Caveatsmentioning
confidence: 99%
“…The distinction between terms was also a recurring topic at C*Sci 2023. The terminology in citizen science has always been a complex issue (Eitzel et al, 2017) and the debate around why the 'citizen' aspect of the term might be insensitive to systematically marginalised populations (Ellwood et al, 2023;Lin Hunter et al, 2023) led to the Citizen Science Association (CSA) changing the conference name to C*Sci (to include both citizen science and community science) and rebranding the CSA itself to become the Association for Advancing Participatory Sciences. For participants to feel included at conferences and to feel that their contributions matter to their fields of research, inclusive terminology is critical (Baeckens et al, 2020;.…”
Section: Inclusion At Conferences In 2023mentioning
confidence: 99%